Fabrication of Alginate and Hydroxyapatite Biocomposite Film for Tissue Regeneration Application - Mashahdi, Nurul Izza; Idris, Maizlinda Izwana (Research Progress in Mechanical and Manufacturing Engineering, 2022)
One of the most promising techniques for bone repair and regeneration of tissue that is difficult to mend on its own is tissue engineering. This research is focusing on the fabrication of alginate hydroxyapatite biocomposite film to enhance tissue regeneration. The objectives for this study are to fabricate alginate hydroxyapatite biocomposite film via solution casting method and to analyse its physicochemical also mechanical properties that is shown via FTIR, AFM and contact angle. The composition of hydroxyapatite was applied at different weight percentage which are from 0.2 wt. %, 0.4 wt. %, 0.6 wt. %, 0.8 wt. % up to 1.0 wt. %. It was revealed that the thickness of fabricated biocomposite films were found between 0.157 mm and 0.232 mm. The viscosity decreased as the weight percentage of the hydroxyapatite increased. For FTIR, the characteristic peaks of PO4-3 and OH- groups which corresponding to hydroxyapatite are existed in the films. For contact angle measure, hydroxyapatite influenced the contact angle measurement and the values decreased compared to the sample with alginate only. AFM shows hydroxyapatite contributes to the rougher surface of the film which this led to the attachment of film to the bone surfaces. Also for swelling studies, the ability of films to swell is also depending on the hydroxyapatite composition. It can be concluded that the alginate and hydroxyapatite biocomposite film has potential in a tissue regeneration application.